Nucleation control of quantum dot synthesis in a microfluidic continuous flow reactor - Kim, Eun Byoel; Tomczak, Kyle M.; Chandrasiri, Hashini B.; Pálmai, Marcell; Ghaznavi, Amirreza; Gritsenko, Dmitry; Xu, Jie; Snee, Preston T. (Frontiers in Nanotechnology, 2023)
The use of microfluidics in chemical synthesis is topical due to the potential to improve reproducibility and the ability promptly interrogate a wide range of reaction parameters, the latter of which is necessary for the training of AI algorithms. Applying microfluidic techniques to semiconductor nanocrystals, or quantum dots (QDs), is challenging due to the need for a high-temperature nucleation event followed by particle growth at lower temperatures. Such a high-temperature gradient can be realized using complex, segmented microfluidic reactor designs, which represents an engineering approach. Here, an alternative chemical approach is demonstrated using the cluster seed method of nanoparticle synthesis in a simple microfluidic reactor system. This enables QD nucleation at lower temperatures due to the presence of molecular organometallic compounds (NMe4)4[Se4Cd10(SPh)16] and (NMe4)4[Se4Zn10(SPh)16]. This integration of cluster seeding with microfluidics affords a new mechanism to tailor the reaction conditions for optimizing yields and tuning product properties.